Thermomechanical analysis and thermal dielectric analysis in pharmacy - Piotr Szynkaruk; Marek Wesołowski (Polish Pharmaceutical Society, 2019)
Methods of thermal analysis, first of all differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA), play an important role in investigation of phase transitions and degradation, that undergo active pharmaceutical ingredients (APIs), excipients and pharmaceutical products under heating or cooling. The most important areas of the DSC and TGA application in the pharmaceutical science and industry include the purity evaluation, the polymorphism and pseudo-polymorphism investigation for proper selection of APIs solid forms, the phase diagrams examination in multicomponent systems, the bioavailability of APIs improvement by formation of cyclodextrins complexes or co-crystals, and the usefulness in preformulation stage of the solid dosage forms, e.g., for study API-excipient compatibility or API-polymer miscibility. However, in the last twenty years more and more articles are published pointing out on potential usefulness of thermomechanical analysis (TMA), dynamic mechanical analysis (DMA) and dielectric analysis (DEA) in the solid dosage technology. The TMA and DMA involve the application of an external force in order to measure the sample deformation. In this way, a rapid and nondestructive method for quantitative investigation of thermo-mechanical and rheological properties of the solid materials has been developed. Consequently, methods of thermomechanical analysis gained increased attention in the pharmaceutical research and dosage form technology to characterize the glass transition temperature and other secondary transitions of the materials (polymers), the miscibility of ingredients in multicomponent systems, the examination of drug delivery systems and their behavior during storage. The DEA, in turn, is commonly used to characterize the glassy (amorphous) and crystalline solid materials using A.C. electrical properties (conductivity) over a wide range of frequencies. For this reason, methods of thermomechanical and dielectric analysis can be successfully used to study the morphological and thermodynamic transitions in APIs and to examine their crystalline and amorphous content in the solid state. For this reason, the aim of this paper was to show a short characteristics of these methods along with the examples which illustrate their potential application in the pharmaceutical science and industry.